Biochar for Improving Soil Biological Properties and Mitigating Salt Stress in Plants on Salt-affected Soils. Issue 2 (19th January 2022) - Egamberdieva, Dilfuza; Alaylar, Burak; Kistaubayeva, Aida; Wirth, Stephan; Bellingrath-Kimura, Sonoko Dorothea
ABSTRACT: Biochar is a solid product obtained by heating of biomass or organic waste in the total or partial absence of oxygen and is applied to improve soil properties, or considered a means of carbon sequestration. Several positive effects of biochar on soil chemical, physical, and biological properties have already been demonstrated. Biochar amendment has also been repeatedly discussed as an effective means to restore saline lands and increase plant tolerance to salt stress. Especially, improved soil cation exchange capacity, water holding capacity, soil nutrient retention, and increased soil enzyme activities and diversity of microbial communities, were reported. However, the underlying mechanisms of such beneficial effects provided by biochar amendment of soils are highly complex. Therefore, more in-depth studies are needed to understand biochar interactions with soil organisms under extreme environments, which will help achieve maximum benefits of biochar under saline soil conditions.